Prevalence, antibiotic profile, virulence determinants, ESBLs, and non-β-lactam encoding genes of MDR Proteus spp. isolated from infected dogs - El-Tarabili, Reham M.; Ahmed, Elsayyad M.; Alharbi, Nada K.; Alharbi, Maha A.; AlRokban, Ahlam H.; Naguib, Doaa; Alhag, Sadeq K.; El Feky, Tamer Mohamed; Ahmed, Ahmed Ezzat; Mahmoud, Ahmed E. (Frontiers in Genetics, 2022)
This study investigated the prevalence, antibiogram, virulence, extended-spectrum β-lactamases (ESBLs), and non-β-lactam encoding genes of Proteus species isolated from infected dogs in Ismailia province, Egypt. The study was conducted on 70 fecal swabs collected from dogs with diarrhea, for bacteriological identification of Proteus spp. The positive isolates were evaluated for antibiotic susceptibility, molecular tests of virulence, ESBLs, and non-β-lactam encoding genes. Prevalence of Proteus spp. was 37.5 % (25/70), including Pro-teus mirabilis (n= 23) and Proteus Vulgaris (n= 2). The Proteus spp. prevalence revealed diversity; high in males than females, in ages < 12 weeks. Investigation of antimicrobial resistance was found against penicillin and amoxicillin (100 %), amoxicillin-clavulanic acid (32 %), Cephalosporins: Cefotaxime and Ceftazidime (36 %), and Monobactam: Aztreonam (28 %) as ESBLs, in addition to tetracycline (32 %) and trimethoprim-sulfamethoxazole (100 %). The strains retrieved by PCR revealed ureC, zapA, and rsbA virulence genes with variant prevalence as; 92 %, 60 %, and 52 %, respectively. Moreover, 28 % (7/25) of recovering strains were MDR up to four classes of antimicrobials, and 48 % (12/25) of the examined strains were MDR up to three antimicrobial classes. In conclusion, to the best of our knowledge, our study could be the first report recording MDR- Proteus spp. in dogs in Egypt.